Juridical Review of The Power Consent Act as Replacement of The Seller's Presence In The Act of Sale and Purchase - Zastis, El Ha; Rokhim, Abdul; Sunardi, Sunardi (Universitas Islam Malang, 2023)
: Power of attorney is a necessity that cannot be avoided in the era of rapid economic progress in Indonesia today. People who will do a sale and purchase of land or property they have of course in good faith, then the sale and purchase must be done with a proof such as an authentic deed. An authentic deed can be obtained if a sale and purchase is carried out by and in the presence, of an authorized official, the land deed making officer (PPAT). Furthermore, if there are parties who cannot sign the AJB, then the power of Attorney becomes the easiest and most efficient solution. The seller who cannot attend an AJB submission in front of PPAT can authorize the person he trusts to act as a substitute for the seller signing the AJB and this can protect the legal interests of thebuyer as well. This study aims to review from sisi the juridical side regarding : (1) What are the legal consequences if the deed of sale and purchase (AJB) is signed by the donee based on the deed of consent of the seller? (2) What is the legal protection for the land deed-making officer (PPAT) who makes a deed of sale and purchase (AJB) signed by another person based on the power of Attorney agreement from the seller? This research method uses yuridis normative juridical approach using legislation and conceptual approach. The results of this study indicate that: first, juridically the deed of approval of the power of attorney used by the donee as a substitute for the presence of the seller is not in violation of the law and legitimate existence as long as its form is an authentic deed and is made in accordance with the provisions of the authentic deed, second, that is perfect evidence for legal protection for the PPAT, the existence of the power of Attorney approval deed and the making of AJB is true according to the authentic deed making protocol otentik. Keywords: Sale Deed and Purchase, Authority Approval Act, Land Deed Office